2022
DOI: 10.3389/fcimb.2021.767576
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Biomarkers and Treatments in Chagas Disease: Insights From TGF-Beta Studies and Immunogenetics

Abstract: The anti-inflammatory cytokine transforming growth factor beta (TGF-β) plays an important role in Chagas disease (CD), a potentially life-threatening illness caused by Trypanosoma cruzi. In this review we revisited clinical studies in CD patients combined with in vitro and in vivo experiments, presenting three main sections: an overview of epidemiological, economic, and clinical aspects of CD and the need for new biomarkers and treatment; a brief panorama of TGF-β roles and its intracellular signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Moreover, there are several studies that show that transforming growth factor beta (TGF-β) modulates the host immune response and inflammation, increases heart fibrosis, stimulates remodeling, and slows heart conduction via gap junction modulation. Pre-clinical studies have shown that TGF-β signaling inhibitors may revert these effects, opening the door to a promising therapeutic approach (Ferreira et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are several studies that show that transforming growth factor beta (TGF-β) modulates the host immune response and inflammation, increases heart fibrosis, stimulates remodeling, and slows heart conduction via gap junction modulation. Pre-clinical studies have shown that TGF-β signaling inhibitors may revert these effects, opening the door to a promising therapeutic approach (Ferreira et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 150 , 151 TGF-β plays a key role in proliferation and differentiation of tissues, as well as in the remodeling of their extracellular matrix. 152 It has also been described to be involved in preventing the development of uncontrolled, potentially life-threatening, inflammatory responses during the acute phases of infection. 19 TGF-β polymorphisms have been associated with increased risk of developing CCC and its expression is greatly increased in the early and chronic stages of T. cruzi infection.…”
Section: Targeting the Pathogenesis Of Chronic Damage As A Complement...mentioning
confidence: 99%
“…T.cruzi , which can penetrate the interstitial vascular system and eventually invade cardiomyocytes, causes heart disease and results in myocardial damage and conduction abnormalities [ 261 , 357 ]. T. cruzi has a highly differential expression of the fibrosis gene, such as metalloproteinase families MMP2, MMP9 and MMP12, as well as abnormal expression of TGF-β, which ultimately causes cardiac fibroblasts to differentiate into myofibroblasts [ 358 – 360 ]. The expression of some novel piRNAs is significantly induced at the early stage of the infection.…”
Section: Biosynthesis and Basic Functions Of Pirnasmentioning
confidence: 99%